Системний аналіз інвестицій в енергоефективність національної економіки - Грицаєнко, Галина Іванівна; Грицаенко, Галина Ивановна; Hrytsaienko, Halyna; Грицаєнко, Ігор Миколайович; Грицаенко, Игорь Николаевич; Hrytsaienko, Ihor (My University, 2021)
UK: У процесі дослідження використано діалектичні методи пізнання, в тому числі монографічний (аналіз публікацій щодо проблем інвестування в енергоефективність) та абстрактно-логічний (теоретичні узагальнення та формулювання висновків) методи. Розглянуто інвестування в енергоефективність як складну, динамічну, ієрархічну систему. Проаналізовані ключові показники енергетики та інвестування в енергоефективність на мега-, макро-, мезо-, мікро- та нанорівні. Елементом наукової новизни є сформульована авторська позиція щодо головних елементів системи інвестицій в енергоефективність та особливості їхнього прояву на різних рівнях національної економіки. Практичною значущістю дослідження є можливість використання одержаних результатів у визначенні шляхів активізації інвестицій в енергоефективність національної економіки. EN: The purpose of the article is to study the problems of investment in energy efficiency of the national economy from the standpoint of systems analysis. The research used dialectical methods of cognition, including monographic (analysis of publications on the problems of investing in energy efficiency) and abstract-logical (theoretical generalizations and formulation of conclusions) methods. Investing in energy efficiency as a complex, dynamic, hierarchical system is considered. Its main elements are objects, tasks and the main goal. Objects of investment in energy efficiency are identified at different levels and subjects of the national economy. The key indicators of energy and investment in energy efficiency at the mega-, macro-, meso-, micro- and nano-levels are analyzed. A comparative analysis of the energy intensity of the world's economies, regions of the world, countries – former republics of the USSR, including Ukraine. The relationships between the amount of total CO2 emissions from the country's GDP and the total supply of primary energy are determined. The tendencies of global investments in clean energy and energy efficiency are studied. Investment projects in the field of renewable energy and energy efficiency in the regions of Ukraine, including Zaporizhia region, as well as in the city of Melitopol and Melitopol region are considered. The main directions of investing in energy efficiency at the nanoscale are identified. An element of scientific novelty is the formulated author's position on the main elements of the system of investments in energy efficiency and the peculiarities of their manifestation at different levels of the national economy. The practical significance of the study is the possibility of using the obtained results in determining ways to increase investment in energy efficiency of the national economy. RU: Цель статьи – исследование проблем инвестиций в энергоэффективность национальной экономики с позиций системного анализа. В процессе исследования использованы диалектические методы познания, в том числе монографический (анализ публикаций по проблемам инвестирования в энергоэффективность) и абстрактно-логический (теоретические обобщения и формулирования выводов) методы. Рассмотрено инвестирование в энергоэффективность как сложную, динамичную, иерархическую систему. Проанализированы ключевые показатели энергетики и инвестирования в энергоэффективность на мега-, макро-, мезо-, микро- и наноуровне. Элементом научной новизны является сформулированная авторская позиция относительно главных элементов системы инвестиций в энергоэффективность и особенностей их проявления на различных уровнях национальной экономики. Практической значимостью исследования является возможность использования полученных результатов в определении путей активизации инвестиций в энергоэффективность национальной экономики.
System analysis of investment in energy efficiency of the national economy
Системный анализ инвестиций в энергоэффективность национальной экономики
Keywords: інвестиції; енергоефективність; системний аналіз; національна економіка; енергозбереження; енергоємність; екологія; investments; energy efficiency; system analysis; national economy; energy saving; energy intensity; ecology; инвестиции; энергоэффективность; системный анализ; национальная экономика; энергосбережение; энергоемкость; экология